Feasibility of successive hydrogen and methane production: Effects of temperature and organic loads on energy potential and microbial dynamics - Devens, Kauanna Uyara; Ribeiro, Alexandre Rodrigues; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Elsevier, 2025)
This study aims to assess the co-digestion of Cassava Wastewater (CW) and glycerol in a two-stage process using fluidized bed reactors (AFBR), verifying the effect of organic loading rate (OLR) and temperature (mesophilic [SMR] and thermophilic [STR]) in sequential reactors on CH4 production. The OLR ranged from 1.2 to 15 g COD.L−1.d−1 and the hydraulic retention time (HRT) was set at 20 h. The mesophilic sequential reactor (MSR) (average temperature of 30 °C) showed greater tolerance to high OLR and its best MPR was 101.12 mL of CH4.d−1.L−1 h−1, obtained at a OLR of 15 g COD.L−1.d−1). The maximum yield was 341.10 mL of CH4.g−1CODcons, found at the OLR of 1.2 g COD.L−1.d−1. The sequential thermophilic reactor (STR) showed the maximum yield and MPR of 333.03 mL of CH4.g−1CODcons (1.2 g COD.L−1.d−1) and 58.84 mL of CH4.d− 1.L−1 h−1 (12 g COD.L−1.d−1), respectively. Through the massive sequencing analysis of the 16S rRNA gene, it was possible to observe a greater diversity of microorganisms in the TSR than in the MSR. A predominance of acetoclastic microorganisms was observed, with the genera Methanobacterium, Methanosarcina and Methanobrevibacter being the most abundant in both reactors. The two-stage system composed of mesophilic acidogenic reactor + MSR was more suitable for the co-digestion of CW and glycerol than the acidogenic reactor + TSR. These results support the notion of standard operating conditions at the industrial plant, where the cassava processing process is carried out at room temperature (25–30 °C).
Keywords: Biodiesel byproduct; Methane; Microbial community; Two-stage system; Wastewater treatment